2018
DOI: 10.1177/1744629518796915
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of obesity interventions targeting anthropometric changes in youth with intellectual disabilities

Abstract: Due to the increased prevalence of obesity and disparity experienced by youth with intellectual disabilities, efforts to synthesize existing knowledge of interventions to attenuate obesity within this marginalized population is imperative. The purpose of this investigation is to systematically analyze interventions targeting anthropometric changes in youth with intellectual disabilities. A search of Cumulative Index of Nursing and Allied Health Literature, Educational Resources Information Center, Medical Lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Historically, a noted limitation within health behaviour research, is that interventions often do not explicitly state the application of a theoretical framework guiding development (Michie et al, 2009 ). Notably, in a recent review of PA‐related obesity interventions in youth with intellectual disabilities, none of the studies explicitly stated the implementation of a theoretical framework (Conrad & Knowlden, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, a noted limitation within health behaviour research, is that interventions often do not explicitly state the application of a theoretical framework guiding development (Michie et al, 2009 ). Notably, in a recent review of PA‐related obesity interventions in youth with intellectual disabilities, none of the studies explicitly stated the implementation of a theoretical framework (Conrad & Knowlden, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to synthesise existing knowledge concerning the effects of exercise interventions on obesity in people with ID have been made (Conrad & Knowlden 2020). Hamilton et al (2007) reviewed the scientific evidence on the effectiveness of interventions for obesity in ID and indicated that PA interventions proved to be effective in the short term and should be considered an essential component of a weight loss programme.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few controlled, multi-component weight loss interventions for young adults with ID found that those enrolled in a 14-week trial using behaviour modification techniques lost more weight than did waitlisted participants, with evidence for continued weight loss during a 5-week maintenance period. 13 Two systematic reviews conducted in 2014 19 and 2018 20 identified only three additional controlled, multi-component interventions; however, one lacked a control group, 21 and one compared the intervention to a historical control group. 22 The third study, a small short-term RCT targeting PA and nutrition that leveraged technology, showed promising results.…”
Section: Introductionmentioning
confidence: 99%